2009
DOI: 10.1177/0885328209344004
|View full text |Cite
|
Sign up to set email alerts
|

The Biocompatibility of Sulfobetaine Engineered Poly (Ethylene Terephthalate) by Surface Entrapment Technique

Abstract: Sulfobetaine-modified poly(ethylene terephthalate) (PET) systems were created by physically entrapping the zwitterionic species on the PET surface. The presence of the sulfobetiane molecules on these surfaces were verified by ATR-FTIR and SEM-EDAX analysis, while wettability of the films was investigated by water contact angle measurements. The blood compatibility of the modified films was evaluated by platelet adhesion in human platelet-rich plasma (PRP). The adhesion and inflammatory response of Mouse RAW 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The surface energy of a solid is usually determined by the study of the contact angles of probe liquids on the solid. There are only a few reports on the surface energies of zwitterionic polymers 49, 50. Hiwatashi et al49 found that the surface energies of ionic random terpolymer films containing the carboxybetaine N ‐(2‐methacryloyloxyethyl)‐ N,N ‐dimethylammonioacetate or the cationic mer N ‐(2‐methacryloyloxyethyl)‐ N,N ‐dimethyl‐ N ‐ethyl ammonium ethyl sulfate ranged from about 38 to 64 mJ/m 2 with a variation in the number of ionic mers from 35 to 60 mol %.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface energy of a solid is usually determined by the study of the contact angles of probe liquids on the solid. There are only a few reports on the surface energies of zwitterionic polymers 49, 50. Hiwatashi et al49 found that the surface energies of ionic random terpolymer films containing the carboxybetaine N ‐(2‐methacryloyloxyethyl)‐ N,N ‐dimethylammonioacetate or the cationic mer N ‐(2‐methacryloyloxyethyl)‐ N,N ‐dimethyl‐ N ‐ethyl ammonium ethyl sulfate ranged from about 38 to 64 mJ/m 2 with a variation in the number of ionic mers from 35 to 60 mol %.…”
Section: Resultsmentioning
confidence: 99%
“…There are only a few reports on the surface energies of zwitterionic polymers. 49,50 Hiwatashi et al 49 found that the surface energies of ionic random terpolymer films containing the carboxybetaine N -(2-methacryloyloxyethyl)-N,N-dimethylammonioacetate or the cationic mer N-(2-methacryloyloxyethyl)- 51 was used to estimate the surface energy (c) values of the BCs. The OWK model resolves surface energy into contributions from dispersion and polar forces, and the work of adhesion at the solid-liquid interface (W SL ) is assumed to be given by the following equation: (2)] relates the work of adhesion to the total surface energies of the solid and liquid (c S and c L , respectively) and the equilibrium contact angle (y) of the liquid on the solid:…”
Section: Surface Energymentioning
confidence: 99%
“…The use of polymers containing zwitterionic groups such as phosphatidylcholines and sulfobetaines, 5-10 which originate from the simulation of biomembranes, 9,11 has been proposed to modify the surface of biomaterials. [12][13][14] A significant reduction in protein adsorption has been demonstrated 5,[8][9][10][12][13][14][15][16][17][18] and attributed to the formation of a hydration layer on the material surface [5][6][7][9][10][11][12][13][14]16,17,19 that prevents the conformational alteration of these proteins. 9,11,13,14,19 Previous researchers 7,13,16,20,21 reported that sulfobetaine application on substrate surfaces reduced bacterial adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…This results in the stable entrapment of the modifying species into the surface of polyurethane. This technique has been applied to modify biomedical polymers such as poly(ethylene terepthalate), poly(methyl methacrylate), and polyurethane 9–11…”
Section: Introductionmentioning
confidence: 99%
“…This technique has been applied to modify biomedical polymers such as poly(ethylene terepthalate), poly(methyl methacrylate), and polyurethane. [9][10][11] Tween80 V R and PLL-RGD modified polyurethane surfaces, which triggered very different biological response in vitro, were selected to represent a broad spectrum of biomaterial applications. 8 In this study, the in vivo foreign body response to these materials was investigated by their implantation in the peritoneal cavity of Wistar rats for a period of 30 days.…”
Section: Introductionmentioning
confidence: 99%